New Version of the COCO Program - Cajka, J.; Fencl, F. (Radioengineering Society, 1994)
The new version of the COCO program enables the analysis of linear circuits in symbolical, symbolic numerical or in semi-symbolical form. Simple synthesis problems can also be solved with the aid of this program. Several examples illustrate the use of the program for circuit analysis and synthesis. Modern network elements (trans-impedance operational amplifier, current conveyors) are built in the program.
Keywords: circuit theory; symbolical network analysis; network functions computation